2000
DOI: 10.4049/jimmunol.164.10.5453
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Functional Anaphylatoxin C5a Receptors on Hepatocytes by In Vivo Treatment of Rats with IL-6

Abstract: In normal rat liver, anaphylatoxin C5a receptors (C5aR) are only expressed by nonparenchymal cells, mainly Kupffer cells and hepatic stellate cells, but not by parenchymal cells, i.e., hepatocytes (HC). Nevertheless, C5a stimulates glucose output by HC. This HC-specific defense reaction is induced indirectly via prostanoids secreted by the C5aR-expressing Kupffer cells and hepatic stellate cells. It is shown here that under inflammatory conditions simulated by in vivo treatment of rats with IL-6 C5aR mRNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…CXCR4 expression is also activated by mutations in genes that alter levels of hypoxiainducible factors, and gene fusion events. Interleukin (IL)-6-induced C5aR expression in rat hepatocytes (37) suggests that C5aR can be expressed in response to specific cytokines that are rich in the cancer microenvironment (20,38). However, IL-6 and IFN-g did not induce C5aR expression in HuCCT1 cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 expression is also activated by mutations in genes that alter levels of hypoxiainducible factors, and gene fusion events. Interleukin (IL)-6-induced C5aR expression in rat hepatocytes (37) suggests that C5aR can be expressed in response to specific cytokines that are rich in the cancer microenvironment (20,38). However, IL-6 and IFN-g did not induce C5aR expression in HuCCT1 cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is characterised as a proinflammatory cytokine primarily because of its role in release of acute-phase proteins (Baumann and Gauldie, 1994;Suffredini et al, 1999) and complement activation (Knittel et al, 1997;Minta et al, 2000;Schieferdecker et al, 2000). In some reports, IL-6 has also been implicated in neutrophil migration (Dalrymple et al, 1995;Romano et al, 1997;Hurst et al, 2001;Suwa et al, 2001) and has been shown to contribute to the rise in circulating neutrophils observed following Photofrin-PDT .…”
Section: Hpph-pdt Induces Local and Systemic Expression Of Il-6mentioning
confidence: 99%
“…Therefore conclusions drawn from results obtained with hepatoma cells should not be extended to wild-type cells without further analyses. For instance, HepG2 cells, FAO, and H4IIE cells express the C5a receptor (CD88) constitutively, but primary HC do not unless they are stimulated with proinflammatory cytokines such as IL-6 or IL-1␤ (Schieferdecker et al, 1997(Schieferdecker et al, , 2000Schlaf et al, 1999).…”
Section: Factor H In Primary Livermentioning
confidence: 99%